Characterizing PSMA heterogeneity in prostate cancer and identifying clinically actionable tumor associated antigens in PSMA negative cases - Yelin Mulati; Qi Shen; Yuxuan Tian; Yuke Chen; Kaifeng Yao; Wei Yu; Yunpeng Cui; Xuedong Shi; Zhisong He; Qian Zhang; Yu Fan (Scientific Reports)
Abstract Prostate-specific membrane antigen (PSMA)-targeted theranostics have profoundly reshaped prostate cancer (PCa) management. However, patterns of PSMA expression heterogeneity and the identification of alternative targets for PSMA-negative cases remain insufficiently understood. To address this gap, this study investigates PSMA expression heterogeneity in 127 primary lesions (PL) from hormone-sensitive PCa (HSPC) cohort and 76 bone metastatic lesions (BML) from metastatic castration-resistant PCa (mCRPC) cohort through immunohistochemical analysis, including 27 matched PL-BML samples. Notable inter-patient variability in PSMA expression was observed, with H-scores ranging from 1.42 to 197.16 overall. Among matched samples, six cases exhibited HSPC-/mCRPC + and seven cases showed HSPC+/mCRPC- PSMA expression patterns. Intra-tumoral heterogeneity was significant, with 67.7% of PL and 30.1% of BML showing high variability in PSMA staining intensity. Membranous PSMA expression and the normalized membrane ratio were significantly higher in PL compared to BML (both p < 0.001). PSMA-negative cases (membranous staining ≤ 20) were found in 15.0% of HSPC and 36.8% of mCRPC cases. PSMA expression levels differed significantly among androgen receptor (AR) expression groups (p < 0.001), with lower PSMA expression associated with lower AR expression levels. Alternative tumor-associated antigens (TAAs) were identified in PSMA-negative cases: B7H3 and TROP2 expression were prominent in HSPC, and STEAP1 and B7H3 expression dominated in mCRPC. These findings highlight the dynamic nature of PSMA expression and support the rationale for exploring alternative theranostic strategies in PSMA-negative PCa.